Interprofessional Collaboration on Drug Administration to Clients with Diabetes Mellitus at Bali Hospital: A Case Study - Afandi, Alfid Tri; Az-Zuhri, Miratul 'Uzaimah; Kurniawan, Dicky Endrian; Muliyanti, Ni Made Arik (D'Nursing and Health Journal (DNHJ), 2023)
Background: Errors in health services in Indonesia are caused by poor communication in implementing interprofessional collaboration with a percentage of 70-80%. This causes medical errors, namely with the percentage distribution of 11% drug administration errors, 46% inappropriate drug use and 54% drug prescribing errors.The purpose of this scientific work is to analyze interprofessional collaboration on drug administration to clients with diabetes mellitus. Method: The method used in this study is observation and measurement tools to evaluate interprofessional collaboration using a checklistSelf-rating score for Interprofessional Collaboration in Clinical Practice. Results: The results obtained are that the application of interprofessional collaboration has not been carried out optimally due to a lack of communication clinical pathway as a guide in carrying out clinical actions, and no health workers have attended IPC (Inter-Professional Collaboration) implementation training.Good communication during the interprofessional collaboration process can solve health problems and improve patient safety. In addition to optimizing the implementation of interprofessional collaboration by holding integrated training to enhance good cooperative relations between professions. Conclusion: Therefore, there is a need for evaluation by services in hospitals regarding interprofessional collaboration as an effort to reduce the risk of errors in administering drugs to patients and improve the quality of health services in hospitals.